Dynamics of Granting Legal Standing to the Indigenous Community in Constitutional Review of Law: Dinamika Pemberian Kedudukan Hukum Pemohon bagi Masyarakat Hukum Adat dalam Pengujian Undang-Undang - Wicaksono, Dian Agung (Constitutional Court of the Republic of Indonesia, Indonesia, 2023)
The research on the existence of Indigenous Community (IC) is interesting to discuss heretofore. Previous studies have discussed the relationship between IC and Constitutional Court (CC) authority in judicial review of the Law (JR). Still, no research has comprehensively mapped the dynamics of granting the Litigants' legal standing to IC in JR since the establishment of CC. This research aims to obtain a portrait of the dynamics and basis of CC for granting legal standing to IC as a Litigant in JR and providing a basic proposal for determining IC’s legal standing as a Litigant in JR. This normative legal research analyzes secondary data by comprehensively mapping decisions on JR with IC as Petitioner since CC was established in 2003 to 2019. The study's results indicate several patterns of legal considerations and the basis of legal considerations for the CC in granting legal standing to IC as Litigants in JR.